Stepping Forward Toward Uniform Sentencing Guidelines for Corporate Criminal Liability: A Theoretical and Practical Legal Review - Dwiarso Budi Santiarto; Maradona; Nur Basuki Minarno (Yuridika, 2026)
The increasing complexity and frequency of corporate crimes in Indonesia has led to a paradigm shift in the national legal system. The absence of sentencing guidelines for corporate crimes has created a legal vacuum, making current regulations inadequate to ensure the consistent and fair imposition of sanctions. Normatively, the recognition that corporations can be held criminally liable is reflected in various regulations, including Code No. 1/2023 and several other sectoral laws governing specific criminal acts. The urgency of developing corporate sentencing guidelines in Indonesia lies in the need to eliminate disparity and legal uncertainty, which otherwise undermines justice for society. The corporate sentencing model must be based on a structured and measurable assessment system, taking into account both objective and subjective variables as stipulated in Article 56 of Code No. 1/2023. This system can be used to assess the degree of fault, the impact of the offense, the role of corporate executives, and the corporation’s attitude during legal proceedings. Furthermore, it can also serve as a reference in determining the criminal threat and the maximum limit of fine categories. Consequently, judges must, going forward, carefully consider whether to impose a criminal penalty or a legal action (choosing one, not both) as a means of protecting society by promoting uniformity and eliminating unwarranted sentencing disparity.